Nursing Home Quality and Financial Performance: Is There a Business Case for Quality? - Weech-Maldonado, Robert (Inquiry, 2019)
This study examines the relationship between nursing home quality and financial performance to assess whether there is a business case for quality. Secondary data sources included the Online Survey Certification and Reporting (OSCAR), Certification and Survey Provider Enhanced Reporting (CASPER), Medicare Cost Reports, Minimum Data Set (MDS 2.0), Area Resource File (ARF), and LTCFocus for all free-standing, nongovernment nursing homes for 2000 to 2014. Data were analyzed using panel data linear regression with facility and year fixed effects. The dependent variable, financial performance, consisted of the operating margin. The independent variables comprised nursing home quality measures that capture the three dimensions of Donabedian’s structure-process-outcomes framework: structure Registered Nurse (RN) hours per resident day, Licensed Practical Nurse (LPN) hours per resident day, Certified Nursing Assistant (CNA) hours per resident day, RN skill mix), process (facility-acquired restraints, facility-acquired catheters, pressure ulcer prevention, and restorative ambulation), and outcomes (facility-acquired contractures, facility-acquired pressure ulcers, hospitalizations per resident, rehospitalizations, and health deficiencies). Control variables included size, average acuity index, market competition, per capita income, and Medicare Advantage penetration rate. This study found that the operating margin was lower in nursing homes that reported higher LPN hours per resident day and higher RN skill mix (structure); higher use of catheters, lower pressure ulcer prevention, and lower restorative ambulation (process); and more residents with contractures, pressure ulcers, hospitalizations and health deficiencies (outcomes). The results suggest that there is a business case for quality, whereas nursing homes that have better processes and outcomes of care perform better financially.